Cortisol reactivity to psychosocial stress in vulnerable and grandiose narcissists: An exploratory study - Borráz-León, Javier I.; Spreitzer, Alena; Scrivner, Coltan; Landers, Mitchell; Lee, Royce; Maestripieri, Dario (Frontiers in Psychology, 2023)
Narcissistic personality manifests itself in at least two different forms: grandiose and vulnerable. In the present study, we compared cortisol and emotional responses to psychosocial stress between subjects high in vulnerable and grandiose narcissism scores, and examined possible associations between narcissism, other personality traits, and stress responses. We hypothesized that subjects with higher scores of vulnerable narcissism would show stronger emotional and physiological reactivity than those with high scores of grandiose narcissism. A final sample of forty-seven participants underwent a Trier Social Stress Test (TSST), provided saliva samples to assess cortisol levels, and completed several personality questionnaires. Consistent with our hypothesis, subjects with higher scores of vulnerable narcissism had a stronger cortisol and emotional response to the those with high scores of grandiose narcissism. Vulnerable narcissism was positively correlated with schizotypal traits, while grandiose narcissism was positively correlated with psychopathic traits. Participants with a mixed-type of narcissism were also discussed. This study provides the first evidence of differential physiological and emotional reactivity to social evaluation threat according to scores of vulnerable and grandiose narcissism. Since this is an exploratory study, the results must be interpreted with caution. However, the results will be informative for future confirmatory research with larger and more heterogeneous samples.